Secular Perspective on The Islamic Political Discourses in Indonesia: A Critical Analysis - Hasbi Aswar (Islamic Research, 2021)
This article aims to critically analyze the secularization perspective on political Islam, focusing on the Indonesian context. The secular perspective has its fundamental doctrine that democracy, separation of State and Religion, and nationalism should be the only system to manage one State. Many people always use kind of argument, even scholars, including in Indonesia, to reject the concept of the Islamic State. This article used descriptive analysis to elaborate the secularization perspective on political Islam in Indonesia and the critical analysis from the Islamic perspective. Furthermore, it also explains the impact of using such a perspective in analyzing the discourse of Political Islam. This article found that the responses of the Muslim figures or people on political Islam in Indonesia are influenced by the secularization perspective instead of using the Islamic perspective. Islamic perspective on political Islam is derived from the Islamic methodology that authoritative scholars have formulated in the past. The secular perspective on politics, as a result, contributed to the decline of the Islamic civilization and colonization from the western power.